2005
DOI: 10.1177/107179190501100202
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Behaviors and Subordinate Resilience

Abstract: Utilizing a sample of 150 part-time MBA students, this study evaluated the relationship between leader behaviors and subordinate resilience. We proposed that the transformational leadership dimensions of Attributed Charisma, Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration, as well as the transactional leadership dimension of Contingent Reward would be positively associated with subordinate resilience. We also proposed that the transactional leadership d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(228 citation statements)
references
References 13 publications
9
181
1
3
Order By: Relevance
“…Previous studies confirmed that resiliency in the workplace can be a good predictor for performance, job attitudes, and other work outcomes (Harland et al 2005). People with high resilience can adapt themselves to changes, and always seek for recognition and exploitation of new idea because of their higher capacity to take risks .…”
Section: The Effect Of Resilience On Innovation In Information Technomentioning
confidence: 76%
“…Previous studies confirmed that resiliency in the workplace can be a good predictor for performance, job attitudes, and other work outcomes (Harland et al 2005). People with high resilience can adapt themselves to changes, and always seek for recognition and exploitation of new idea because of their higher capacity to take risks .…”
Section: The Effect Of Resilience On Innovation In Information Technomentioning
confidence: 76%
“…Moreover, transformational leaders are excellent motivators because they emphasize on the people more than results. The behaviors of transformational leadership are consist of employees developing and treating, problem solving, others interesting, creative promotions and adaptive solutions, others respect, others confidence, achievement focusing, common benefit focusing, optimistic focusing, enthusiastic focusing, and self-actualization focusing (Harland et al, 2005). Goodwin, Whittington, and Wofford (2001) suggested that transformational leadership style of the full-range leadership model is the culmination of many leadership theories.…”
Section: Transformational Leadership Stylesmentioning
confidence: 99%
“…Of particular relevance to businesses, companies, and the military are findings that resilience is related to workplace performance [13,15,17,[36][37][38]. In a workplace context, resilience has been re-defined as the "positive psychological capacity to rebound, or 'bounce back' from adversity, uncertainty, conflict, failure or even positive change, progress, and increased responsibility" [39] (p. 702).…”
Section: Resiliencementioning
confidence: 99%